EQUATING VILLA WITH “HOUSE” IN AGGRAVATED THEFT OFFENSE - Peter Jeremiah Setiawan; Xavier Nugraha; Widyanti Wibowo (Lambung Mangkurat Law Journal, 2021)
One of the places that is often targeted by thieves is in a villa. In Article 363 paragraph (1) 3 of the Criminal Code, there is a regulation related to theft with a aggravating if the theft is carried out at night in a house or closed yard where the house is, but there is no provision that explicitly states that it is related to theft in a villa. Based on this background, the formulation of the objectives of this article is to understand: 1. What are the elements of the aggravated theft offense ? 2. Can a villa be conaidered with a “house” as an element of the aggravated theft offense ? This research is a normative legal research with statutory, conceptual, and case approaches. Based on the analysis in this article, it can be understood that 1. The elements in the offense are the same as ordinary theft, but there are additional elements that are alternative. 2. The theft in a villa at night can be qualified for theft with a aggravating factor as stipulated in Article 363 paragraph (1) of the Criminal Code, on the basis of socio-historical interpretation and extensive interpretation.